Study on Li + uptake by lithium ion-sieve via the pH technique - Wang, Lu; Meng, Chang Gong; Ma, Wei (Colloids and surfaces. A, Physicochemical and engineering aspects, 2009)
The Li + uptake was studied by two lithium ion-sieves with different properties (surface, crystal configuration, and grain size). The reaction of Li + uptake was investigated in batch experiments via the pH technique. Equilibrium studies were performed in solution pH 7, 10, 12 and the Langmuir equation was applied to the data. The results indicated that there was strong responsive behavior of Li + uptake to pH in neutral or weak alkaline solutions, and Li + uptake could not proceed completely for reason of pH descent with proton releasing from ion-sieves. Sieve-2 had faster Li + uptake rate than Sieve-1 owing to the quicker intraparticle diffusion in the small grain. The Li +–H + ion-exchange was accepted as the main mechanism of Li + uptake by spinel-type manganese oxide with manganese valence nearly equals to +4. Furthermore, it suggested that Li + uptake by ion-sieves would be necessary to study in buffer solution.